2002
DOI: 10.1046/j.1532-5415.2002.50310.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dementia in Older People in an Urban Population of Korea: The Seoul Study

Abstract: The prevalence of dementia in older people in Seoul appears to be somewhat lower than in rural areas of Korea. Considering the difficulties involved in establishing a diagnostic threshold for dementia, actual differences in dementia prevalence between Asian populations are probably minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 39 publications
6
73
3
1
Order By: Relevance
“…Although one study has previously been published on the incidence of AD in Korea [5,6], the estimate may not represent the incidence of AD in the elderly Korean population and requires verification as the study was conducted in a rural population and the estimated incidence of AD was much higher than that of other Asian and Western countries [7,8,9]. Many potential risk factors for AD reported in previous prevalence studies [2,10,11,12] have never been verified by prospective incidence studies in Korea.…”
Section: Introductionmentioning
confidence: 97%
“…Although one study has previously been published on the incidence of AD in Korea [5,6], the estimate may not represent the incidence of AD in the elderly Korean population and requires verification as the study was conducted in a rural population and the estimated incidence of AD was much higher than that of other Asian and Western countries [7,8,9]. Many potential risk factors for AD reported in previous prevalence studies [2,10,11,12] have never been verified by prospective incidence studies in Korea.…”
Section: Introductionmentioning
confidence: 97%
“…The differences in these prevalence estimates of dementia may be due to different population characteristics or differences in study methodologies, such as case-finding procedures and the diagnostic threshold for dementia [7] . Furthermore, although the two previous studies on the prevalence of dementia in urban Korean elders were conducted in the two largest metropolitan cities of Korea (Seoul [3] and Busan [2] ), the study populations were not representative of the typical urban elderly population in Korea. In particular, the level of educational attainment, one of major sources of variation in dementia prevalence, was much lower in the studied samples than among Korean urban elders in general [2,3,8] .…”
Section: Prevalence Of Dementia In Korean Eldersmentioning
confidence: 99%
“…Two population-based epidemiological studies [2,3] previously reported the prevalence of dementia to be 7.2 and 8.1% in urban Korean elderly populations. These rates were higher than those reported from urban populations of other Asian and western countries [1,[4][5][6] .…”
Section: Prevalence Of Dementia In Korean Eldersmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the subjects were community-dwelling elderly, aged 55 or over, who enrolled in the Korean Longitudinal Study on Health and Aging and the Seoul Study [11] .…”
Section: Methodsmentioning
confidence: 99%